Comparative aspects of blood coagulation measurements in various wild and captive bird species - Guddorf, Vanessa; Rohn, Karl; Kummerfeld, Norbert; Mischke, Reinhard (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2017)
Objective: Information about the influence of species variety or diseases on coagulation values in avian blood is rare. The aim of this study was to assess the influence of species on measurements of coagulation parameters in avian plasma samples using commercially available reagents and to investigate potential influences of selected diseases on clotting times. Material and methods: Prothrombin time (PT), activated partial thromboplastin time (aPTT) and thrombin time (TT) were measured in citrated plasma of healthy individuals collected from eight different wild and captive avian species applying currently commercially available reagents prepared for use in humans, which were preselected in preliminary studies. The same parameters were tested in plasma samples from birds affected by aspergillosis, atherosclerosis, neoplasia and traumata. Results: PT and aPTT showed a high interspecies variety. Irrespective of species, aPTTs were extremely long and partially exceeded the measurement range limit. Minor variations between species were seen in TT measurements. Clotting times obtained from birds affected by aspergillosis, atherosclerosis and neoplasia were not significantly different when compared to healthy birds. Plasma obtained from traumatised individuals showed significantly shorter PT and aPTT than that in healthy birds. Conclusion and clinical relevance: Differences between species must be considered in diagnostic coagulation measurements in avian blood. Regardless of the avian species, aPTT measurements on avian samples appear to be of limited value. Lower PT and aPTT values reflect coagulation activation in traumatised birds.
Keywords: Haemostasis; birds; prothrombin time; activated partial thromboplastin time; thrombin time; species variety